Liquidity, corporate governance and firm performance: A meta-analysis - Ngoc Phuong Anh Nguyen; Thi Thanh Binh Dao (Cogent Business & Management, 2022)
Our study investigates the interlink between liquidity, corporate governance and firm value with the adoption of meta-analysis. The final sample consists of 428 studies extracted from 55 papers, covering 632,196 firm-year observations in a worldwide scope. The diversity in data is believed to reduce possible homogeneity due to regional or time period concentration. Using random-effects model, it is reported that both illiquidity factors (Spread and Amihud illiquidity) can significantly worsen the performance of a firm, while the corporate governance-firm value connection is significantly positive via three out of four factors (Corporate governance index, Board size and Institutional ownership). Besides studying the overall relationship direction, the paper also looks into its heterogeneity. The existence of heterogeneity is confirmed in both liquidity-firm value and governance-firm value relationships. The running of meta-regression indicates that both illiquidity factors are significantly moderated by most of the examined paper characteristics, whilst only two out of four corpor ate governance indicators (Corporate governance index and Institutional ownership) are significantly altered.
Keywords: 650; corporate governance; firm performance; liquidity; meta-analysis; moderators